2017
DOI: 10.1177/0960327117730880
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the neutralizing potency of antisera raised against native and γ-irradiated Naja nigricollis (black-necked spitting cobra) venom in rabbits, concerning its cardiotoxic effect

Abstract: The present study was designed to prepare a specific safe antiserum for Naja nigricollis using γ-irradiated (1.5KGy and3KGy) venoms. Rabbits were used for active immunization using irradiated venoms (1.5 and 3 kGy) as a toxoid, mice were used for determination of LD50 post immunization and the rats were used for neutralization of the cardiotoxic effect of venom. Results of the immunodiffusion test indicated that the sera of rabbits raised against non-irradiated, 1.5- and 3-kGy γ-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(48 reference statements)
0
5
0
1
Order By: Relevance
“…Ionizing radiation has been studied over the years for causing changes in the structure of proteins and for contributing to decrease the toxicity of molecules [59][60][61]. This conformational change and fragmentation occur through degradation and other actions caused by the direct and indirect action of ionizing radiation, where direct effects of radiation are caused when gamma rays and high-energy electrons interact directly with molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ionizing radiation has been studied over the years for causing changes in the structure of proteins and for contributing to decrease the toxicity of molecules [59][60][61]. This conformational change and fragmentation occur through degradation and other actions caused by the direct and indirect action of ionizing radiation, where direct effects of radiation are caused when gamma rays and high-energy electrons interact directly with molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of TeNT for the production and commercialization of vaccines and the promising use of ionizing radiation for the improvement of immunogens and the proposal of new vaccine candidates, since these irradiated molecules demonstrated an improvement in their immunogenic properties and a robust immune response without the use of adjuvants and chemical treatments for inactivation, the objective of this study was to evaluate the effect of 60 Co gamma radiation on concentrated (unpurified) TeNT and its residual enzymatic activity following irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, elapidaes express neurotoxic venoms. However, these ophidia never cease to evolve surprises as it have been showed that the venom of the black-necked spitting cobra, Naja nigricollis demonstrated cardiotoxic effects [43,44]. In another twist, the following African spitting cobras, Naja mossambica, N. nigricincta, N. nigricollis, N. pallid, N. ashei, N. katiensis, and N. nubiae demonstrated potent anticoagulant activity in their venom arising from strong inhibition of Factor Xa [45,46].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…A third venom-dependent approach that has been investigated has included chemical deactivation of whole venom or toxin fractions used to generate antiserum with an increased neutralization capacity, by enabling higher immunization dosages due to lowered toxicity. This deactivation has been mediated by gamma radiation [ 156 , 157 , 158 , 159 ], reaction with glutaraldehyde [ 160 , 161 , 162 , 163 ], iodination [ 164 , 165 ], alkylation [ 166 ], or reaction with formaldehyde [ 119 ]. In 1998, very high neutralization capacities were reported by Heneine & Heneine, who used rabbit antiserum to neutralize up to 30 LD 50 s of T. serrulatus scorpion venom in vitro [ 165 ].…”
Section: Alternative Venom-dependent Immunization Approachesmentioning
confidence: 99%